Medication Adherence Associated with Tuberculosis Knowledge and Treatment Duration among Pulmonary Tuberculosis Patients at a TB DOTS Clinic in Jakarta, Indonesia - Saraswati, Andini; Ramadhan, Gaung Eka; Junalia, Elly; Maryati, Maryati (Jurnal Kesehatan dan Kedokteran, 2026)
This study aimed to analyze medication adherence among pulmonary tuberculosis patients by examining the roles of patients’ knowledge level and treatment duration within a TB DOTS clinical setting. Methodology: A quantitative analytic study with a cross-sectional design was conducted among 89 pulmonary tuberculosis patients at the TB DOTS Clinic of Pasar Minggu Regional General Hospital. Data were collected using structured questionnaires and clinical records. Univariate analysis described respondent characteristics, while bivariate analysis using the Chi-Square test examined the relationships between study variables. Findings: The results showed that most patients demonstrated poor knowledge of tuberculosis and associated with levels of medication adherence. A statistically significant relationship was found between patients’ knowledge and medication adherence, indicating that higher knowledge levels were associated with better adherence. In contrast, treatment duration was not significantly associated with medication adherence. Implications: These findings highlight the importance of strengthening patient education within tuberculosis control programs, as improved knowledge may enhance adherence and support successful treatment outcomes. Originality: This study provides empirical evidence from a real-world DOTS clinical setting by integrating patient knowledge and treatment duration in adherence analysis. The findings demonstrate that patient knowledge may play a more influential role than treatment duration in shaping medication adherence, offering a patient-centered contribution to tuberculosis care research.